Branding Activities for Raja Ampat Geopark Development in the Pentahelix Model Perspective - Hadija Mawaddah; Bambang Dwi Prasetyo; Ananda Sabil Hussein (Journal La Sociale, 2024)
The creation of parks as a significant endeavor to enhance the worth of tourism sites has emerged as a prominent phenomenon that garners global attention. The Raja Ampat Geopark has initiated branding efforts to position itself as an exceptionally distinctive tourism attraction in Indonesia. Collaboration amongst stakeholders is essential and cannot be disregarded. This research seeks to ascertain the branding activities involved in establishing the Raja Ampat Geopark, as well as the specific roles played by each partner, utilizing the Penta helix model and collaboration theory. The constructivist paradigm is employed to comprehend the process of knowledge generation inside the Penta helix model. The research findings indicate that successful geopark branding relies on a strong partnership between the government, universities, the tourism industry, local communities, and digital media. Integrating promotion with the preservation of nature and culture in a branding plan effectively enhances awareness and fosters a favorable perception of the Raja Ampat Geopark in a sustainable manner. While the Raja Ampat Geopark has experienced a notable increase in tourism, there are difficulties in effectively managing the balance between this growth and the preservation of the environment, which is crucial for ensuring a sustainable future. This study enhances the progress of geopark development and sustainable tourism by emphasizing the significant role of collaboration and branding based on the Penta helix model. Additional study is required to offer efficient recommendations for the establishment of parks in the future.